Oral tuberculosis mimicking malignancy - Ajay Kumar Verma; Ved Prakash; Rashmi Upadhyay; Surya Kant; Ankit Bhatia (Wolters Kluwer Medknow Publications, 2015)
The presentation of a non-healing friable ulcerated growth in the oral cavity with cervical lymph nodes in an elderly patient, would in all possibilities, raise the first suspicion of malignancy. We present a case of an ulcerative nonhealing growth over the hard palate and left gingivobuccal sulcus, the biopsy of which revealed granulomatous lesions, leading to the suspicion of oral tuberculosis. The importance of early diagnosis and treatment lies in the fact that it can be easily confused with neoplastic or traumatic etiologies